Self-Acceptance Journey Of Day Danainut In Last Twilight Series (2023): A Queer Study - Rachel Aurelia Rahmadita (Samudra Ilmu Indonesia, 2026)
The representation of queer and disabled identities in contemporary media has increasingly attracted scholarly attention. However, limited studies have explored how these intersecting identities contribute to the process of self-acceptance. This article examines the self-acceptance journey of Day Danainut, the protagonist of the Thai television series Last Twilight (2023), through the perspective of Judith Butler's queer theory. Employing a qualitative textual analysis, the study investigates selected scenes, dialogues, and cinematic elements, including mise-en-scène, sound, and visual composition, to understand how Day negotiates his identity within ableist and heteronormative social structures. The analysis is organised around three interconnected concepts derived from Butler's work—recognition, performativity, and subversion—which are examined as mutually constitutive processes rather than sequential stages. The findings demonstrate that Day's self-acceptance develops through continuous negotiation between social expectations and personal agency. His identity is repeatedly shaped by experiences of recognition and misrecognition, performed through everyday interactions, and reconstructed through acts that challenge dominant norms surrounding disability and sexuality. Rather than portraying self-acceptance as an individual psychological achievement, Last Twilight presents it as a socially negotiated process emerging from the intersection of queer identity and disability. By integrating queer theory with disability studies and film analysis, this article contributes to expanding discussions of intersectional identity in contemporary media and offers an alternative perspective on how self-acceptance is represented through ongoing identity negotiation.